Cytologic findings of mammary analogue secretory carcinoma arising in the thyroid. Issue 6 (2nd March 2017) - Rodríguez‐Urrego, Paula A.; Dogan, Snjezana; Lin, Oscar
Abstract : Mammary analogue secretory carcinoma (MASC) of the salivary gland, first described by Skálová et al in 2010, is a tumor that morphologically and genetically resembles breast secretory carcinoma harboring ETV6‐NTRK3 fusion gene. To date, only seven cases of primary thyroid MASC have been described. The overall findings are similar to those seen in the salivary gland counterpart including the ETV6‐NTRK3 fusion gene. This is the second report describing the cytologic features of MASC at this primary location, which also showed a classical type papillary carcinoma component. Diagn. Cytopathol. 2017;45:552–556. © 2017 Wiley Periodicals, Inc.